Effect of method of preparation on hydrodesulphurization activity of Co- or Ni-promoted MoS2/SBA-15 catalysts - Garg, Shelu; Soni, Kapil; Prasad, V. V. D. N.; Kumar, Manoj; Bhaskar, Thallada; Gupta, J. K.; Dhar, G. Murali; Gopinath, Chinnakonda S. (Journal of Chemical Sciences, 2014)
Ordered mesoporous material SBA-15 was synthesized and used as a support for the preparation of molybdenum sulphide catalysts through precipitation from homogeneous solution (PFHS) technique with the Mo content varying from 2-12 wt%. The prepared catalysts were evaluated for thiophene hydrodesulphurizadon catalytic activities at 400 degrees C. Catalysts prepared through PFHS method resulted in highly dispersed MoS2 catalysts, which were inferred from powder X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), low temperature oxygen chemisorptions (LTOC) and BET surface area analysis. The relationship between XPS intensity ratio, oxygen chemisorption and catalytic activities is discussed in terms of highly dispersed nano particles of MoS2 and its consequence in accommodating more promoted atoms at the edge sites.
Keywords: HDS; MoS2; PFHS method; promotional effects; SBA-15